The mummy - Sutherland, Doris J. (Devil's advocates., 2019)
Released in 1932, The Mummy moved Universal horror into a land of deserts, pyramids, and long-lost tombs. This book examines the roots of The Mummy. It shows how the film shares many motifs with the work of writers such as H. Rider Haggard and discusses how The Mummy drew upon a contemporary vogue for all things ancient Egyptian.